APAKAH LUKISAN MERUPAKAN MEDIA INVESTASI? - Gatot Sujono (Akutansi Bisnis & Manajemen ( ABM ), 2002)
Triggered by an unpredictable monetary problem, most of Asian countries has plunged into deep economic crisis causing sluggish real-sector development even with negative rate. The secondary effect of the crisis has been rampant in the capital-stock market which has fluctuated at low levels. Conversely, during the last two decade the global art market, especially paintings, has expanded enormously with fascinating price and sales. As an illustration, during the two weeks in November 1990, Sothebys and Christie' New York together took transactions amounted to $355.6 million. Another example, in December 2000 Christies London was able to sell ?Portrait of a Lady aged 62'? by Rembrant Harmensz van Rijn for 19,803,751.00 (www.christies.com), These interesting phenomena give the big question mark: is the art marketable and profitable ? Therefore, this study attempts to analyze whether paintings considered as profitable alternative media of investment. Using a simple regression analysis, this study shows that paintings --in general-- give the acceptable normal rate of return .